Resin foam
The resin foam addresses the challenge of combining high shock absorption with display stability by specifying mechanical properties like compression load and stress retention, ensuring effective shock absorption and display clarity in thin devices.
Patent Information
- Application Number
- JP2021561445
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-25
- Filing Date
- 2020-11-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-11-25
AI Technical Summary
Existing resin foams struggle to provide both high shock absorption and prevent display unevenness in thin electronic devices due to pressure, particularly in narrow clearances, with existing technologies either focusing on shock absorption or display issues but not both effectively.
A resin foam with specific mechanical properties including a 50% compression load of 5N/cm² to 30N/cm², compressive stress retention rates of 50% or more after 6 and 12 hours, and a cellular structure, along with a thickness recovery rate of 75% or more, which balances shock absorption with display stability.
The resin foam effectively absorbs shocks while preventing display unevenness in thin electronic devices by maintaining structural integrity and recovering from deformation, ensuring clear and uniform display quality.
Smart Images

Figure 0007611853000002 
Figure 0007611853000003 
Figure 0007611853000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin foam. [Background technology]
[0002] Resin foams are widely used as cushioning materials for protecting the screens and substrates of electronic devices, etc. In recent years, in response to the trend toward thinner electronic devices, cushioning materials are required to exhibit high shock absorption properties even when placed in locations with narrow clearances.
[0003] In addition, in touch panel type liquid crystal display devices such as smartphones and mobile terminals, the alignment of liquid crystal molecules in the liquid crystal panel can become disordered due to the bending that occurs when a user presses the screen, resulting in display unevenness (ripple-like bleeding patterns; so-called pooling). This phenomenon has become particularly problematic with the recent trend toward thinner devices.
[0004] Cited Document 1 discloses a foam sheet having good shock absorption and anti-pooling properties that can quickly eliminate pooling that occurs. However, even with this technology, it is difficult to prevent pooling itself from occurring. Patent Document 2 discloses a foam that improves stress dispersion and is less likely to cause display unevenness on a panel, but does not disclose anything about shock absorption. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP2007-016070A [Patent Document 2] International Publication WO12 / 133288 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a resin foam which is thin, has excellent shock absorption properties, and is capable of preventing display unevenness due to pressure when applied to an image display device. [Means for solving the problem]
[0007] The resin foam of the present invention has a 50% compression load of 5N / cm 2 ~30N / cm 2 The compressive stress retention rate after 6 hours is 50% or more, the compressive stress retention rate after 12 hours is 50% or more, and the compressive stress retention rate has a cellular structure. In one embodiment, the resin foam has a 50% compression load of 10 N / cm 2 ~30N / cm 2 It is. In one embodiment, the resin foam has a compressive modulus of elasticity of 200 kPa or more. In one embodiment, the resin foam has an unfoamed bending stress of 5 MPa or more. In one embodiment, the resin foam has a thickness change rate due to repeated compression of 10% or less. In one embodiment, the resin foam has an apparent density of 0.02 g / cm 3 ~0.50g / cm 3 It is. In one embodiment, the resin foam has a thickness recovery rate of 75% or more. In one embodiment, the resin foam has cells with an aspect ratio of 1.5 or more. In one embodiment, the resin foam has an average cell diameter of 10 μm to 200 μm. In one embodiment, the resin foam has a foam ratio of 30% or more. In one embodiment, the resin foam has a coefficient of variation of cell diameter of 0.5 or less. In one embodiment, the resin foam has a cell wall thickness of 0.1 μm to 10 μm. In one embodiment, the resin foam contains a polyolefin-based resin. In one embodiment, the polyolefin-based resin is a mixture of a polyolefin other than the polyolefin-based elastomer and a polyolefin-based elastomer. In one embodiment, the resin foam has a heat-fusible layer on one or both sides. According to another aspect of the present invention, there is provided a foam material having a resin foam layer and a pressure-sensitive adhesive layer disposed on at least one side of the resin foam layer, the resin foam layer being the above-mentioned resin foam. Effect of the Invention
[0008] It is possible to provide a resin foam that is thin, has excellent shock absorption properties, and is capable of preventing display unevenness due to pressure when applied to an image display device. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view of a foam member according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a stress relaxation tester. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A. Resin foam The resin foam of the present invention has a 50% compression load of 5N / cm 2 ~30N / cm 2 The compressive stress retention rate after 6 hours is 50% or more, and the compressive stress retention rate after 12 hours is 50% or more. The resin foam of the present invention has a cell structure. Examples of the cell structure include a closed cell structure, an open cell structure, and a semi-open semi-closed cell structure (a cell structure in which a closed cell structure and an open cell structure are mixed). The cell structure of the resin foam is preferably an open cell structure or a semi-open semi-closed cell structure, and more preferably a semi-open semi-closed cell structure. The resin foam of the present invention is obtained by foaming a resin composition. The resin composition is a composition containing at least a resin constituting the resin foam.
[0011] As described above, the 50% compression load of the resin foam of the present invention is 5 N / cm 2 ~30N / cm 2 Within this range, a resin foam having appropriate hardness, which is resistant to compressive deformation even when subjected to a high impact force and has excellent shock absorption properties can be obtained. In addition, a resin foam can be obtained in which the repulsive force when applied to a gap (particularly a gap with a narrow clearance) is appropriately suppressed, preventing adverse effects on surrounding components. Furthermore, if the 50% compression load is within the above range, a resin foam can be obtained that can prevent display unevenness caused by pressure when applied to an image display device, for example, color unevenness caused by disturbance of liquid crystal alignment when a liquid crystal display device is touched. When the 50% compression load is 5 N / cm 2 If the compressive load is less than 7 N / cm, compression deformation is likely to occur, and there is a risk that display unevenness due to pressure when applied to an image display device cannot be prevented. 2 ~30N / cm 2 and more preferably 10 N / cm 2 ~30N / cm 2 and more preferably 10 N / cm 2 ~25N / cm 2 and particularly preferably 10 N / cm 2 ~20N / cm 2 Within this range, the above-mentioned effects become prominent.
[0012] As described above, the compressive stress retention rate of the resin foam of the present invention after 6 hours is 50% or more. Within this range, a resin foam that is difficult to deform and can be favorably restored even if deformed can be obtained. When such a resin foam is applied to an image display device, it can prevent display unevenness due to pressure, for example, color unevenness due to disturbance of liquid crystal alignment when a liquid crystal display device is touched. The compressive stress retention rate of the resin foam after 6 hours is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. Within this range, the above effect is remarkable. The upper limit of the compressive stress retention rate after 6 hours is, for example, 95% (preferably 98%). The compressive stress retention rate after 6 hours is calculated from the compressive stress (N1) immediately after compressing a test piece of 30 mm x 30 mm size to a compression rate of 50% at a compression speed of 10 mm / min, and the compressive stress (N2) after maintaining 50% compression for 6 hours, according to the formula N2 / N1 x 100.
[0013] As described above, the compressive stress retention rate of the resin foam of the present invention after 12 hours is 50% or more. Within this range, a resin foam that is difficult to deform and can be favorably restored even if deformed can be obtained. When such a resin foam is applied to an image display device, it can prevent display unevenness due to pressure, for example, color unevenness due to disturbance of liquid crystal alignment when a liquid crystal display device is touched. The compressive stress retention rate of the resin foam after 12 hours is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. Within this range, the above effect is remarkable. The upper limit of the compressive stress retention rate after 12 hours is, for example, 95% (preferably 98%). The compressive stress retention rate after 12 hours is calculated from the compressive stress (N1) immediately after compressing a test piece of 30 mm x 30 mm size to a compression rate of 50% at a compression speed of 10 mm / min, and the compressive stress (N2) after maintaining 50% compression for 12 hours, according to the formula N2 / N1 x 100.
[0014] The resin foam of the present invention, which has a 50% compressive load and a compressive stress retention rate within the above ranges, has a predetermined hardness, is difficult to deform, and is easy to recover even if it is deformed. Such a resin foam has excellent shock absorption properties and can prevent color unevenness caused by disturbance of liquid crystal alignment when a liquid crystal display device is touch-operated.
[0015] The apparent density of the resin foam of the present invention is preferably 0.02 g / cm 3 ~0.50g / cm 3 If the density is within this range, a resin foam excellent in flexibility and stress dispersibility can be obtained. The apparent density of the resin foam of the present invention is more preferably 0.04 g / cm 3 ~0.4g / cm 3 and more preferably 0.06 g / cm 3 ~0.3g / cm 3 and more preferably 0.08 g / cm 3 ~0.25g / cm 3 and particularly preferably 0.1 g / cm 3 ~0.2g / cm 3 and most preferably 0.13 g / cm 3 ~0.2g / cm 3 If the density is within this range, the above-mentioned effect becomes significant. The method for measuring the apparent density will be described later.
[0016] The 25% compression load of the resin foam is preferably 3N / cm 2 Within this range, the effects of the present invention are remarkable. The 25% compressive load of the resin foam is preferably 3.2 N / cm 2 More preferably, it is 3.5 N / cm 2 More preferably, it is 4N / cm 2 The upper limit of the 25% compression load of the resin foam is, for example, 10 N / cm 2 (Preferably 20N / cm 2 The method for measuring the 25% compression load conforms to the method for measuring the compression hardness of foamed materials described in JIS K 6767.
[0017] The compressive elastic modulus of the resin foam is preferably 200 kPa or more. In this range, a resin foam that is unlikely to undergo compression deformation even when subjected to a high impact force and is unlikely to be crushed can be obtained. The compressive elastic modulus of the resin foam is preferably 220 kPa or more, more preferably 250 kPa or more, and even more preferably 300 kPa or more. In this range, the above effects are remarkable. The upper limit of the compressive elastic modulus of the resin foam is preferably 1000 kPa, more preferably 800 kPa, and even more preferably 600 kPa. The compressive elastic modulus of the resin foam is calculated from F(5%) and F(15%) by the formula (F(15%)-F(5%)) / (15-5)×100, by measuring the compressibility (%) and compressive repulsion (kPa) of the resin foam based on the compression test section of JIS K 6767, reading the compressive repulsion F(5%) at a compression rate of 5% and the repulsion F(15%) at a compression rate of 15%, respectively.
[0018] The elastic strain energy of the resin foam of the present invention during compression is preferably 10 kPa or more. The "elastic strain energy during compression" refers to the total amount of compression repulsion force when the resin foam is compressed by 10%. Specifically, the "elastic strain energy during compression" is determined from a compression ss curve with the x-axis representing the compression rate (%) and the y-axis representing the compression repulsion force (kPa) when the compressibility (%) and compression repulsion force (kPa) of the resin foam are measured by a compression test (test temperature: 23°C, sample size: 10 mm x 10 mm, compression speed: 10 mm / min) in accordance with JIS K 6767, and is the area of a region defined by the ss curve and the x-axis in a range of compression rate of 0% to 10%. If the elastic strain energy during compression of the resin foam is within the above range, a resin foam having excellent impact absorption properties can be obtained. More specifically, a resin foam having an elastic strain energy within the above range can absorb even a strong impact well because a lot of energy is consumed for deformation of the resin foam when an impact is applied. The elastic strain energy of the resin foam of the present invention when compressed is more preferably 20 kPa or more, even more preferably 30 kPa or more, even more preferably 50 kPa or more, even more preferably 60 kPa or more, even more preferably 80 kPa or more, particularly preferably 100 kPa or more, and most preferably 150 kPa or more. Within such a range, the above-mentioned effects become prominent. The upper limit of the elastic strain energy of the resin foam of the present invention when compressed is, for example, 500 kPa (preferably 800 kPa).
[0019] The non-foaming bending stress of the resin foam of the present invention is preferably 5 MPa or more, more preferably 6 MPa or more, even more preferably 9 MPa or more, and particularly preferably 10 MPa or more. Within such a range, a large energy is required to deform the bubble walls (cell walls) of the resin foam, and a resin foam having excellent impact absorption can be obtained. The resin foam of the present invention can improve impact resistance (shock absorption) by appropriately reducing the flexibility that has been important in the past in cushioning materials and balancing it with other properties. The resin foam of the present invention, which exhibits impact absorption by such a different action from the past, is particularly useful in a configuration in which impact propagates in a narrow range (a configuration in which impact is difficult to spread in the planar direction), and is particularly useful when applied to a flexible member (for example, a member made of resin). The upper limit of the non-foaming bending stress is preferably 20 MPa, more preferably 15 MPa. Within such a range, a resin foam having excellent flexibility and stress dispersion can be obtained. "Non-foamed bending stress" refers to the bending stress of a resin molded body a that has been returned to a bubble-free non-foamed state (bulk) by hot pressing a resin foam. The density of the resin molded body a can be made equivalent to the density of a resin molded body b before foaming that is formed from a resin composition described below. The bending stress of the resin molded body a (non-foamed bending stress of the resin foam) can be made equivalent to that of the resin molded body b. The method for measuring the bending stress will be described below.
[0020] The impact absorption rate of the resin foam is preferably 25% or more, more preferably 30% or more, and further preferably 35% or more. The impact absorption rate is measured as follows. A test specimen was formed by placing a resin foam, double-sided tape (product number: No. 5603W, Nitto Denko), and PET film (product number: Diafoil MRF75, Mitsubishi Plastics) on top of the impact force sensor in that order. A 66g iron ball was dropped onto the test specimen from a height of 50cm above the PET film to measure the impact force F1. · Also, drop an iron ball directly onto the impact force sensor as described above to measure the impact force F0 of the blank. Calculate the shock absorption rate (%) from F1 and F0 using the formula (F0-F1) / F0×100.
[0021] The thickness recovery rate of the resin foam is preferably 75% or more, more preferably 80% or more, and further preferably 85% or more. The thickness recovery rate of the foam layer is defined by the following formula. This thickness recovery rate of the foam layer is a recovery rate measured by applying a load to a foam sheet with a certain area to compress it, and is different from the so-called dent recovery rate measured by applying a load locally to dent only a part of it. Thickness recovery rate (%) = {(thickness 0.5 seconds after releasing the compression state) / (initial thickness)} x 100 Initial thickness: The thickness of the resin foam before a load is applied. Thickness 0.5 seconds after releasing the compression: 1000g / cm2 for resin foam 2 The thickness of the resin foam is measured 0.5 seconds after the load is applied and maintained for 120 seconds, and then the compression is released.
[0022] The thickness change rate of the resin foam of the present invention due to repeated compression is preferably 10% or less. Within this range, it is possible to obtain a resin foam that is resistant to crushing, can prevent gaps with surrounding members when used as a cushioning material, and has excellent dust resistance. The thickness change rate of the resin foam due to repeated compression is more preferably 8% or less, even more preferably 5% or less, particularly preferably 3% or less, and most preferably 1% or less. Within this range, the above-mentioned effects become more pronounced. The smaller the thickness change rate of the resin foam due to repeated compression, the more preferable it is, and the lower limit is, for example, 0.5% (preferably 0.3%, more preferably 0.1%, and even more preferably 0.05%). The thickness change rate of the resin foam due to repeated compression was measured using a disk jig with a flat tip (contact area: 4.9 cm 2 ) is pressed against a resin foam and a 50% compression / 10% compression (thickness basis) cycle is performed 5,000 times. The change in thickness is calculated by the formula {(thickness before test)-(thickness after test)} / (thickness before test)×100.
[0023] The tensile modulus of the resin foam at 23°C is preferably 0.6 MPa or more, more preferably 0.7 MPa to 5 MPa, and more preferably 1 MPa to 4 MPa. Within such ranges, a resin foam that is excellent in stress dispersion and can exhibit excellent impact absorption even in a thin film can be obtained. The tensile modulus is determined by fixing a sample (size: 10 mm x 80 mm) with a chuck distance of 40 mm and performing a tensile test at a tensile speed of 500 mm / min to obtain a tensile strain-tensile strength curve, and by the slope of the straight line connecting the origin of this curve and the tensile strength at a tensile strain of 10%.
[0024] The elongation at break of the resin foam at 25°C is preferably 120% or less, more preferably 110% or less, even more preferably 100% or less, and particularly preferably 90% or less. Within such a range, a resin foam having excellent flexibility and stress dispersion can be obtained. If the elongation at break is small, the cell walls of the resin foam are less deformed when a load is applied to the resin foam. For example, when a filler is added, slippage is more likely to occur at the interface between the resin constituting the resin foam and the filler, and the load can be more easily relaxed. On the other hand, if the elongation at break is too large, the cell walls of the resin foam are more deformed, which may make it difficult to relax the load. The elongation at break can be measured in accordance with JIS K 6767.
[0025] The tensile stress retention of the resin foam is preferably 60% or more, more preferably 63% to 100%, and even more preferably 63% to 95%. Within such a range, a resin foam can be obtained that is excellent in stress dispersion and can exhibit excellent impact absorption even in a thin film. In this specification, the tensile stress retention is the ratio of the tensile strength immediately after stretching a resin foam (width 10 mm x length 100 mm) by 20% in the length direction at a speed of 300 m / min to the tensile strength after 12 hours of holding after stretching (tensile strength after 12 hours / tensile strength immediately after stretching x 100).
[0026] The thickness of the resin foam is preferably 30 μm to 5000 μm, more preferably 35 μm to 4000 μm, even more preferably 40 μm to 3000 μm, even more preferably 45 μm to 2000 μm, particularly preferably 50 μm to 1000 μm, and most preferably 55 μm to 500 μm. As described above, the resin foam of the present invention exhibits excellent impact resistance even though it is a thin layer. In addition, if the thickness of the resin foam is within the above range, a fine and uniform cell structure can be formed, which is advantageous in that excellent impact absorption can be exhibited.
[0027] The resin foam has an average bubble diameter (average cell diameter) of preferably 10 μm to 200 μm, more preferably 15 μm to 180 μm, even more preferably 20 μm to 150 μm, even more preferably 23 μm to 120 μm, particularly preferably 25 μm to 100 μm, and most preferably 30 μm to 80 μm. Within such a range, a resin foam can be obtained that does not deform excessively when subjected to an impact and can exhibit high impact absorption properties. In addition, the resin foam has an appropriate hardness and is suitable as a cushioning material for filling gaps. A method for measuring the average bubble diameter will be described later.
[0028] The aspect ratio of the bubbles in the resin foam is preferably 1.5 or more. Within this range, a resin foam having excellent thickness recovery can be obtained. The aspect ratio of the bubbles constituting the resin foam is preferably 2.0 or more, more preferably 2.5 or more. Within this range, the above effects are remarkable. The upper limit of the aspect ratio of the bubbles constituting the resin foam is preferably 5, more preferably 4, and even more preferably 3.5. Within this range, a resin foam having excellent impact absorption can be obtained.
[0029] In this specification, the "aspect ratio of the cells in a resin foam" refers to the aspect ratio of a given area (3 mm 2The aspect ratio of each bubble present in the resin foam is determined in the following manner. The resin foam is cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction), and cut into pieces of a specified area (3 mm 2 ) area is observed at a magnification of 100x. The length of one bubble in the thickness direction and the length TD are measured. The same measurement is performed for all bubbles present within a specified area. The aspect ratio of a bubble is calculated by dividing the TD length by the thickness direction length. The same calculation is performed for all bubbles, and the average value is the "aspect ratio of bubbles in the resin foam."
[0030] The coefficient of variation of the bubble diameter (cell diameter) of the resin foam of the present invention is preferably 0.5 or less, more preferably 0.48 or less, even more preferably 0.45 or less, particularly preferably 0.43 or less, and most preferably less than 0.4. Within such a range, deformation due to impact becomes uniform, local stress load is prevented, and a resin foam having excellent stress dispersion and particularly excellent impact resistance can be obtained. The smaller the coefficient of variation, the more preferable it is, and the lower limit is, for example, 0.2 (preferably 0.15, more preferably 0.1, and even more preferably 0.01). A method for measuring the coefficient of variation of the bubble diameter will be described later.
[0031] The foaming rate (cell rate) of the resin foam of the present invention is preferably 30% or more, more preferably 50% or more. Within this range, a resin foam having a small rebound stress during compression can be obtained. When the resin foam is applied to a place with a small clearance by compressing it slightly, the stress applied to other members can be reduced. For example, when the resin foam is applied to a display member, the stress applied to the display member can be relaxed and dispersed, which is useful from the viewpoint of reducing color unevenness and protecting the member. The upper limit of the foaming rate is preferably 99% or less, more preferably 95% or less, and even more preferably 90% or less. Within this range, the resin foam has a moderate hardness, a small amount of deformation when impacted, and therefore has high impact absorption. The method for measuring the foaming rate will be described later.
[0032] The thickness of the cell walls of the resin foam of the present invention is preferably 0.1 μm to 10 μm, more preferably 0.3 μm to 8 μm, even more preferably 0.5 μm to 5 μm, particularly preferably 0.7 μm to 4 μm, and most preferably 1 μm to 3 μm. Within such a range, a resin foam that does not deform excessively when subjected to impact and can exhibit high impact absorption properties can be obtained. In addition, a resin foam that has appropriate hardness and is suitable as a cushioning material for filling gaps can be obtained. A method for measuring the thickness of the cell walls will be described later.
[0033] When the cell structure of the resin foam of the present invention is a semi-open, semi-closed cell structure, the ratio of the closed cell structure therein is preferably 40% or less, more preferably 30% or less. Within such a range, the resin foam has a suitable hardness and can be used as a cushioning material for filling gaps. In this specification, the closed cell ratio of the resin foam is determined, for example, by immersing a measurement object in water in an environment of a temperature of 23°C and a humidity of 50%, measuring the mass thereafter, and then sufficiently drying the object in an oven at 80°C, and then measuring the mass again. In addition, since open cells can hold moisture, the mass of the open cells is measured and determined.
[0034] The resin foam of the present invention may have any appropriate shape depending on the purpose, and a representative example of such a shape is a sheet.
[0035] The resin foam of the present invention may have a heat-melting layer on one or both sides thereof. A resin foam having a heat-melting layer can be obtained, for example, by rolling a resin foam (or a precursor of a resin foam) using a pair of heating rolls heated to a temperature equal to or higher than the melting temperature of the resin composition constituting the resin foam.
[0036] The resin foam of the present invention can be formed by any appropriate method as long as the effects of the present invention are not impaired. A representative example of such a method is a method of foaming a resin composition containing a resin material (polymer).
[0037] A-1. Resin composition The resin foam of the present invention can be typically obtained by foaming a resin composition. The resin composition contains any appropriate resin material (polymer).
[0038] Examples of the polymer include acrylic resins, silicone resins, urethane resins, polyolefin resins, ester resins, rubber resins, etc. The polymers may be used alone or in combination of two or more.
[0039] The content of the polymer is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, further preferably 40 to 80 parts by weight, and particularly preferably 40 to 60 parts by weight, relative to 100 parts by weight of the resin composition. If the content is within such a range, a resin foam having superior flexibility and stress dispersion can be obtained.
[0040] In one embodiment, a polyolefin resin is used as the polymer.
[0041] The content of the polyolefin resin is preferably 50 parts by weight to 100 parts by weight, more preferably 70 parts by weight to 100 parts by weight, even more preferably 90 parts by weight to 100 parts by weight, particularly preferably 95 parts by weight to 100 parts by weight, and most preferably 100 parts by weight, relative to 100 parts by weight of the above polymer.
[0042] The polyolefin resin is preferably at least one selected from the group consisting of polyolefins and polyolefin elastomers, and more preferably, polyolefins and polyolefin elastomers are used in combination. The polyolefins and polyolefin elastomers may each be used alone or in combination of two or more. In this specification, the term "polyolefin" does not include "polyolefin elastomers".
[0043] When polyolefin and polyolefin elastomer are used in combination as the polyolefin resin, the weight ratio of polyolefin to polyolefin elastomer (polyolefin / polyolefin elastomer) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, further preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30. Within such a range, the effects of the present invention are remarkable.
[0044] As the polyolefin, any suitable polyolefin may be adopted as long as it does not impair the effects of the present invention. Examples of such polyolefin include linear polyolefin and branched (branched) polyolefin. In one embodiment, a branched polyolefin is used as the polyolefin-based resin. In this embodiment, only a branched polyolefin may be used as the polyolefin, or a branched polyolefin and a linear polyolefin may be used in combination. By using a branched polyolefin, a resin foam having a small average cell diameter and excellent impact resistance can be obtained. The content of the branched polyolefin is preferably 30 parts by weight to 100 parts by weight, more preferably 80 parts by weight to 120 parts by weight, based on 100 parts by weight of the polyolefin.
[0045] The polyolefin may be, for example, a polymer containing a structural unit derived from an α-olefin. The polyolefin may be composed of only a structural unit derived from an α-olefin, or may be composed of a structural unit derived from an α-olefin and a structural unit derived from a monomer other than an α-olefin. When the polyolefin is a copolymer, any suitable copolymerization form may be adopted as the copolymerization form. For example, a random copolymer, a block copolymer, etc. may be mentioned.
[0046] The α-olefin that can constitute the polyolefin is preferably, for example, an α-olefin having 2 to 8 carbon atoms (preferably 2 to 6, more preferably 2 to 4) (e.g., ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, etc.). Only one type of α-olefin may be used, or two or more types of α-olefins may be used.
[0047] Examples of monomers other than α-olefins constituting polyolefins include ethylenically unsaturated monomers such as vinyl acetate, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, vinyl alcohol, etc. The monomers other than α-olefins may be of only one type or of two or more types.
[0048] Specific examples of polyolefins include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene (propylene homopolymer), copolymers of ethylene and propylene, copolymers of ethylene and an α-olefin other than ethylene, copolymers of propylene and an α-olefin other than propylene, copolymers of ethylene, propylene and an α-olefin other than ethylene and propylene, and copolymers of propylene and an ethylenically unsaturated monomer.
[0049] In one embodiment, a polypropylene-based polymer having a propylene-derived structural unit is used as the polyolefin. Examples of the polypropylene-based polymer include polypropylene (propylene homopolymer), a copolymer of ethylene and propylene, and a copolymer of propylene and an α-olefin other than propylene, and preferably polypropylene (propylene homopolymer). The polypropylene-based polymer may be used alone or in combination of two or more kinds.
[0050] The melt flow rate (MFR) of the polyolefin at a temperature of 230° C. is preferably 0.2 g / 10 min to 10 g / 10 min, more preferably 0.25 g / 10 min to 5 g / 10 min, further preferably 0.3 g / 10 min to 3 g / 10 min, and particularly preferably 0.35 g / 10 min to 1.5 g / 10 min, in order to more effectively exhibit the effects of the present invention. In this specification, the melt flow rate (MFR) refers to the MFR measured at a temperature of 230° C. and a load of 2.16 kgf according to ISO1133 (JIS-K-7210).
[0051] In one embodiment, two or more polyolefins having different melt flow rates (MFR) at a temperature of 230° C. within the above range are used in combination. In this case, a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.2 g / 10 min or more and less than 0.7 g / 10 min (more preferably 0.2 g / 10 min to 0.65 g / 10 min) and a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.7 g / 10 min to 10 g / 10 min (more preferably 0.7 g / 10 min to 5 g / 10 min, even more preferably 0.7 g / 10 min to 3 g / 10 min, particularly preferably 0.7 g / 10 min to 1.5 g / 10 min, and most preferably 0.7 g / 10 min to 1.3 g / 10 min) can be used in combination. In this way, a resin foam having a small average cell diameter and excellent impact resistance can be obtained.
[0052] When two or more polyolefins having different melt flow rates (MFR) at a temperature of 230° C. within the above range are used in combination as the polyolefin, for example, a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.2 g / 10 min or more and less than 0.7 g / 10 min (more preferably 0.2 g / 10 min to 0.65 g / 10 min) and a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.7 g / 10 min to 10 g / 10 min (more preferably 0.7 g / The weight ratio of the polyolefin (usually 0.10 min to 5 g / 10 min, more preferably 0.7 g / 10 min to 3 g / 10 min, particularly preferably 0.7 g / 10 min to 1.5 g / 10 min, and most preferably 0.7 g / 10 min to 1.3 g / 10 min) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, still more preferably 20 / 80 to 80 / 20, particularly preferably 30 / 70 to 70 / 30, and most preferably 40 / 60 to 60 / 40.
[0053] As the polyolefin, commercially available products may be used, such as "E110G" (manufactured by Prime Polymer Co., Ltd.), "EA9" (manufactured by Japan Polypropylene Corporation), "EA9FT" (manufactured by Japan Polypropylene Corporation), "E-185G" (manufactured by Prime Polymer Co., Ltd.), "WB140HMS" (manufactured by Borealis), and "WB135HMS" (manufactured by Borealis).
[0054] As the polyolefin-based elastomer, any suitable polyolefin-based elastomer may be adopted within the scope of not impairing the effects of the present invention. Examples of such polyolefin-based elastomers include so-called non-crosslinked thermoplastic olefin-based elastomers (TPOs) such as ethylene-propylene copolymers, ethylene-propylene-diene copolymers, ethylene-vinyl acetate copolymers, polybutene, polyisobutylene, chlorinated polyethylene, elastomers in which a polyolefin component and a rubber component are physically dispersed, and elastomers in which a polyolefin component and a rubber component have a microphase separation structure; dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) which are multiphase polymers obtained by dynamically heat treating a mixture containing a resin component A (olefin-based resin component A) forming a matrix and a rubber component B forming a domain in the presence of a crosslinking agent, and which have a sea-island structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in the resin component A which is a matrix (sea phase); and the like.
[0055] The polyolefin-based elastomer preferably contains a rubber component. Examples of such rubber components include those described in JP-A-08-302111, JP-A-2010-241934, JP-A-2008-024882, JP-A-2000-007858, JP-A-2006-052277, JP-A-2012-072306, JP-A-2012-057068, JP-A-2010-241897, JP-A-2009-067969, and JP-A-03 / 002654.
[0056] Specific examples of elastomers having a microphase-separated structure of a polyolefin component and an olefin-based rubber component include elastomers made of polypropylene resin (PP) and ethylene-propylene rubber (EPM), elastomers made of polypropylene resin (PP) and ethylene-propylene-diene rubber (EPDM), etc. The weight ratio of the polyolefin component to the olefin-based rubber component (polyolefin component / olefin-based rubber) is preferably 90 / 10 to 10 / 90, more preferably 80 / 20 to 20 / 80.
[0057] Dynamically crosslinked thermoplastic olefin elastomers (TPV) generally have a higher elastic modulus and smaller compression set than non-crosslinked thermoplastic olefin elastomers (TPO), which gives them good recovery properties and allows them to show excellent recovery properties when foamed.
[0058] As described above, dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) are obtained by dynamically heat treating a mixture containing a resin component A (olefin-based resin component A) that forms a matrix and a rubber component B that forms domains, in the presence of a crosslinking agent. These TPVs are multiphase polymers having an island-sea structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in resin component A, which is the matrix (sea phase).
[0059] Examples of dynamically crosslinked thermoplastic olefin-based elastomers (TPVs) include those described in JP-A-2000-007858, JP-A-2006-052277, JP-A-2012-072306, JP-A-2012-057068, JP-A-2010-241897, JP-A-2009-067969, and JP-A-03 / 002654.
[0060] As the dynamically crosslinked thermoplastic olefin-based elastomer (TPV), commercially available products may be used, such as "Zeotherm" (manufactured by Zeon Corporation), "Thermorun" (manufactured by Mitsubishi Chemical Corporation), and "Sarlink 3245D" (manufactured by Toyobo Co., Ltd.).
[0061] The melt flow rate (MFR) of the polyolefin elastomer at a temperature of 230°C is preferably 2 g / 10 min to 15 g / 10 min, more preferably 3 g / 10 min to 10 g / 10 min, even more preferably 3.5 g / 10 min to 9 g / 10 min, particularly preferably 4 g / 10 min to 8 g / 10 min, and most preferably 4.5 g / 10 min to 7.5 g / 10 min.
[0062] The melt tension (190° C., at break) of the polyolefin elastomer is preferably less than 10 cN, and more preferably from 5 cN to 9.5 cN.
[0063] The JIS A hardness of the polyolefin elastomer is preferably 30° to 95°, more preferably 35° to 90°, further preferably 40° to 88°, particularly preferably 45° to 85°, and most preferably 50° to 83°. The JIS A hardness is measured based on ISO7619 (JIS K6253).
[0064] In one embodiment, the resin foam (i.e., the resin composition) may further contain a filler. By including a filler, it is possible to form a resin foam that requires a large amount of energy to deform the cell walls, and the resin foam exhibits excellent impact absorption properties. Furthermore, by including a filler, it is possible to form a fine and uniform cell structure, which is advantageous in that excellent impact absorption properties can be exhibited. Only one type of filler may be used alone, or two or more types may be used in combination.
[0065] The content of the filler is preferably 10 to 150 parts by weight, more preferably 30 to 130 parts by weight, and further preferably 50 to 100 parts by weight, relative to 100 parts by weight of the polymer constituting the resin foam. If the content is within such a range, the above-mentioned effects become prominent.
[0066] In one embodiment, the filler is an inorganic material. Examples of materials constituting the inorganic filler include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, silicon nitride, boron nitride, crystalline silica, amorphous silica, metal (e.g., gold, silver, copper, aluminum, nickel), carbon, graphite, etc.
[0067] In one embodiment, the filler is an organic material. Examples of materials constituting the organic filler include polymethylmethacrylate (PMMA), polyimide, polyamideimide, polyetheretherketone, polyetherimide, and polyesterimide.
[0068] A flame retardant may be used as the filler. Examples of the flame retardant include bromine-based flame retardants, chlorine-based flame retardants, phosphorus-based flame retardants, and antimony-based flame retardants. From the viewpoint of safety, a non-halogen, non-antimony-based flame retardant is preferably used.
[0069] Examples of non-halogen, non-antimony flame retardants include compounds containing aluminum, magnesium, calcium, nickel, cobalt, tin, zinc, copper, iron, titanium, boron, etc. Examples of such compounds (inorganic compounds) include hydrated metal compounds such as aluminum hydroxide, magnesium hydroxide, magnesium oxide-nickel oxide hydrate, and magnesium oxide-zinc oxide hydrate.
[0070] The filler may be subjected to any suitable surface treatment, such as a silane coupling treatment or a stearic acid treatment.
[0071] The bulk density of the filler is preferably 0.8 g / cm 3 More preferably, it is 0.6 g / cm or less. 3or less, and more preferably 0.4 g / cm 3 or less, and particularly preferably 0.3 g / cm 3 Within this range, the filler can be contained with good dispersibility, and the effect of adding the filler can be fully exhibited even with a small filler content. A resin foam with a small filler content is advantageous in that it is highly foamed, flexible, and has excellent stress dispersion and appearance. The lower limit of the bulk density of the filler is, for example, 0.01 g / cm. 3 and preferably 0.05 g / cm 3 and more preferably 0.1 g / cm 3 It is.
[0072] The number average particle size (primary particle size) of the filler is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. Within such a range, the filler can be contained with good dispersibility and a uniform cell structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The lower limit of the number average particle size of the filler is, for example, 0.1 μm. The number average particle size of the filler can be measured using a particle size distribution meter (MicrtracII, Microtrack Bell Co., Ltd.) using a suspension prepared by mixing 1 g of filler in 100 g of water as a sample.
[0073] The specific surface area of the filler is preferably 2 m 2 / g or more, more preferably 4m 2 / g or more, more preferably 6m 2 Within this range, the filler can be incorporated with good dispersibility and a uniform cell structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The upper limit of the specific surface area of the filler is, for example, 20 m 2 The specific surface area of the packing material can be measured by the BET method, that is, by adsorbing a molecule with a known adsorption area onto the packing material surface at a low temperature using liquid nitrogen, and measuring the amount of the molecule adsorbed.
[0074] The resin composition may contain any other appropriate components as long as the effects of the present invention are not impaired. Such other components may be one type only, or two or more types. Examples of such other components include rubber, resins other than the polymers blended as the resin material, softeners, aliphatic compounds, antiaging agents, antioxidants, light stabilizers, weathering agents, UV absorbers, dispersants, plasticizers, carbon, antistatic agents, surfactants, crosslinking agents, thickeners, rust inhibitors, silicone compounds, tension modifiers, shrinkage inhibitors, flow modifiers, gelling agents, curing agents, reinforcing agents, foaming agents, foam nucleating agents, colorants (pigments, dyes, etc.), pH adjusters, solvents (organic solvents), thermal polymerization initiators, photopolymerization initiators, lubricants, crystal nucleating agents, crystallization accelerators, vulcanizing agents, surface treatment agents, and dispersion aids.
[0075] A-2. Formation of resin foam The resin foam of the present invention is typically obtained by foaming a resin composition. As the foaming method (cell formation method), a method usually used in foam molding, such as a physical method or a chemical method, can be adopted. That is, the resin foam of the present invention may typically be a foam formed by foaming using a physical method (physical foam), or a foam formed by foaming using a chemical method (chemical foam). The physical method is generally a method in which a gas component such as air or nitrogen is dispersed in a polymer solution and bubbles are formed by mechanical mixing (mechanical foam). The chemical method is generally a method in which cells are formed by gas generated by thermal decomposition of a foaming agent added to a polymer base, to obtain a foam.
[0076] The resin composition to be subjected to foam molding may be prepared, for example, by mixing the components using any appropriate melt kneading device, such as an open-type mixing roll, a non-open-type Banbury mixer, a single-screw extruder, a twin-screw extruder, a continuous kneader, or a pressure kneader.
[0077] <Embodiment 1 for forming resin foam of the present invention> One example of an embodiment 1 for forming a resin foam of the present invention is a form in which a resin foam is formed through a step (step A) of mechanically foaming an emulsion resin composition (an emulsion containing a resin material (polymer) etc.). Examples of foaming devices include high-speed shear devices, vibration devices, and pressurized gas discharge devices. Of these foaming devices, high-speed shear devices are preferred from the viewpoints of miniaturizing the bubble diameter and producing a large volume. One example of an embodiment 1 for forming a resin foam of the present invention is applicable to formation from any resin composition.
[0078] From the viewpoint of film-forming properties, the solids concentration of the emulsion is preferably high. The solids concentration of the emulsion is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 50% by weight or more.
[0079] The bubbles generated by mechanical stirring are gases that have been taken into the emulsion. Any suitable gas may be used as the gas as long as it is inert to the emulsion and does not impair the effects of the present invention. Examples of such gases include air, nitrogen, and carbon dioxide.
[0080] The resin foam of the present invention can be obtained by applying the foamed emulsion resin composition (bubble-containing emulsion resin composition) onto a substrate and drying it (Step B). Examples of the substrate include a release-treated plastic film (such as a release-treated polyethylene terephthalate film), a plastic film (such as a polyethylene terephthalate film), and the like.
[0081] In step B, any appropriate method may be adopted as the coating method and drying method as long as the effects of the present invention are not impaired. Step B preferably includes a preliminary drying step B1 in which the bubble-containing emulsion resin composition applied to the substrate is dried at 50° C. or higher and lower than 125° C., and a main drying step B2 in which the composition is further dried at 125° C. or higher and 200° C. or lower.
[0082] By providing the preliminary drying step B1 and the main drying step B2, it is possible to prevent the coalescence of bubbles and the bursting of bubbles due to a sudden rise in temperature. In particular, in a foamed sheet having a small thickness, the coalescence and bursting of bubbles due to a sudden rise in temperature is likely to occur, so providing the preliminary drying step B1 is very significant. The temperature in the preliminary drying step B1 is preferably 50°C to 100°C. The time for the preliminary drying step B1 is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes. The temperature in the main drying step B2 is preferably 130°C to 180°C or less, more preferably 130°C to 160°C. The time for the main drying step B2 is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.
[0083] <Embodiment 2 for forming resin foam of the present invention> In one embodiment 2 of the present invention, a resin foam is formed by foaming a resin composition with a foaming agent. As the foaming agent, a foam that is usually used for foam molding can be used, and from the viewpoints of environmental protection and low pollution to the foamed object, it is preferable to use a high-pressure inert gas.
[0084] As the inert gas, any suitable inert gas may be adopted as long as it is inert to the resin composition and can be impregnated. Examples of such inert gas include carbon dioxide, nitrogen gas, and air. These gases may be used in combination. Among these, carbon dioxide is preferred from the viewpoint of a large amount of impregnation into the resin material (polymer) and a fast impregnation speed.
[0085] The inert gas is preferably in a supercritical state. That is, it is particularly preferable to use carbon dioxide in a supercritical state. In a supercritical state, the solubility of the inert gas in the resin composition is increased, making it possible to mix the inert gas at a high concentration, and the inert gas becomes highly concentrated when the pressure is suddenly lowered, so that more bubble nuclei are generated, and the density of the bubbles formed by the growth of the bubble nuclei is larger than in other states even if the porosity is the same, so that fine bubbles can be obtained. The critical temperature of carbon dioxide is 31°C, and the critical pressure is 7.4 MPa.
[0086] Examples of the method for forming a foam by impregnating a resin composition with a high-pressure inert gas include a gas impregnation step in which an inert gas is impregnated under high pressure into a resin composition containing a resin material (polymer), a depressurization step in which the pressure is reduced after the gas impregnation step to foam the resin material (polymer), and a heating step in which bubbles are grown by heating as necessary. In this case, a previously molded unfoamed molded body may be impregnated with an inert gas, or a molten resin composition may be impregnated with an inert gas under pressure and then molded during depressurization. These steps may be performed by either a batch method or a continuous method. That is, the resin composition may be molded into an appropriate shape such as a sheet to form an unfoamed resin molded body, and then the unfoamed resin molded body is impregnated with a high-pressure gas and foamed by releasing the pressure, or the resin composition may be kneaded with a high-pressure gas under pressure, and molded and foamed at the same time by releasing the pressure.
[0087] An example of producing a foam by the batch method is shown below. For example, a resin sheet for foam molding is produced by extruding a resin composition using an extruder such as a single screw extruder or a twin screw extruder. Alternatively, the resin composition is uniformly kneaded using a kneader equipped with blades such as a roller, a cam, a kneader, or a Banbury type, and pressed to a predetermined thickness using a hot plate press or the like to produce an unfoamed resin molded body. The unfoamed resin molded body thus obtained is placed in a high-pressure container, and high-pressure inert gas (such as carbon dioxide in a supercritical state) is injected to impregnate the unfoamed resin molded body with the inert gas. When the inert gas is sufficiently impregnated, the pressure is released (usually to atmospheric pressure), and bubble nuclei are generated in the resin. The bubble nuclei may be allowed to grow at room temperature as they are, or may be allowed to grow by heating in some cases. As a heating method, known or commonly used methods such as a water bath, an oil bath, a heated roll, a hot air oven, far infrared rays, near infrared rays, and microwaves can be used. After the bubbles are grown in this manner, the foam can be obtained by rapidly cooling the foam with cold water or the like to fix the shape. The unfoamed resin molded product to be foamed is not limited to a sheet-like product, and various shapes can be used depending on the application. The unfoamed resin molded product to be foamed can be produced by other molding methods such as extrusion molding, press molding, and injection molding.
[0088] An example of producing a foam by a continuous method is shown below. For example, a resin composition is kneaded using an extruder such as a single-screw extruder or a twin-screw extruder while injecting (introducing) a high-pressure gas (particularly an inert gas, or further carbon dioxide) to sufficiently impregnate the resin composition with the high-pressure gas in a kneading impregnation step, and the resin composition is extruded through a die or the like provided at the tip of the extruder to release the pressure (usually to atmospheric pressure), and foaming and foaming are simultaneously performed in a molding decompression step to form the foam. In addition, when foaming in a continuous method, a heating step for growing bubbles by heating may be provided as necessary. After the bubbles are grown in this way, the shape may be fixed by rapidly cooling with cold water or the like as necessary. The high-pressure gas may be introduced continuously or discontinuously. In addition, in the kneading impregnation step and the molding decompression step, for example, an extruder or an injection molding machine may be used. In addition, as a method of heating when growing bubble nuclei, any appropriate method such as a water bath, an oil bath, a heat roll, a hot air oven, far infrared rays, near infrared rays, and microwaves may be used. The foam may have any suitable shape, such as a sheet, a prismatic shape, a cylindrical shape, or an irregular shape.
[0089] The amount of gas mixed when foam molding the resin composition is preferably 2% by weight to 10% by weight, more preferably 2.5% by weight to 8% by weight, and even more preferably 3% by weight to 6% by weight, based on the total amount of the resin composition, in order to obtain a highly foamed product.
[0090] The pressure when the resin composition is impregnated with the inert gas can be appropriately selected in consideration of operability and the like. For example, such a pressure is preferably 6 MPa or more (for example, 6 MPa to 100 MPa), and more preferably 8 MPa or more (for example, 8 MPa to 50 MPa). In addition, the pressure when carbon dioxide in a supercritical state is used is preferably 7.4 MPa or more from the viewpoint of maintaining the supercritical state of carbon dioxide. If the pressure is lower than 6 MPa, the bubble growth during foaming is remarkable, and the bubble diameter becomes too large, so that a preferable average cell diameter (average bubble diameter) may not be obtained. This is because, when the pressure is low, the amount of gas impregnated is relatively small compared to that at high pressure, and the bubble nucleation rate decreases and the number of bubble nuclei formed decreases, so that the amount of gas per bubble increases conversely and the bubble diameter becomes extremely large. In addition, in a pressure range lower than 6 MPa, the bubble diameter and bubble density change significantly even with a small change in the impregnation pressure, so that it is easy to make it difficult to control the bubble diameter and bubble density.
[0091] The temperature in the gas impregnation step varies depending on the type of inert gas used and the type of components in the resin composition, and can be selected from a wide range. In consideration of operability, the temperature is preferably 10°C to 350°C. The impregnation temperature when impregnating an inert gas into an unfoamed molded body is preferably 10°C to 250°C, more preferably 40°C to 230°C, in the batch process. In addition, the impregnation temperature when extruding a molten polymer impregnated with a gas to simultaneously perform foaming and molding is preferably 60°C to 350°C in the continuous process. When carbon dioxide is used as the inert gas, the temperature during impregnation is preferably 32°C or higher, more preferably 40°C or higher, in order to maintain a supercritical state.
[0092] In the depressurizing step, the depressurizing speed is preferably 5 MPa / sec to 300 MPa / sec in order to obtain uniform fine bubbles.
[0093] The heating temperature in the heating step is preferably 40°C to 250°C, and more preferably 60°C to 250°C.
[0094] B. Foam material 1 is a schematic cross-sectional view of a foam member according to one embodiment of the present invention. The foam member 100 has a resin foam layer 10 and a pressure-sensitive adhesive layer 20 disposed on at least one side of the resin foam layer 10. The resin foam layer 10 is composed of the above-mentioned resin foam.
[0095] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 300 μm, more preferably 6 μm to 200 μm, further preferably 7 μm to 100 μm, and particularly preferably 8 μm to 50 μm. When the thickness of the pressure-sensitive adhesive layer is within the above range, the foam material of the present invention can exhibit excellent impact absorption properties.
[0096] The adhesive layer may be a layer made of any suitable adhesive. Examples of the adhesive constituting the adhesive layer include rubber-based adhesives (synthetic rubber-based adhesives, natural rubber-based adhesives, etc.), urethane-based adhesives, acrylic urethane-based adhesives, acrylic-based adhesives, silicone-based adhesives, polyester-based adhesives, polyamide-based adhesives, epoxy-based adhesives, vinyl alkyl ether-based adhesives, fluorine-based adhesives, and rubber-based adhesives. The adhesive constituting the adhesive layer is preferably at least one selected from acrylic-based adhesives, silicone-based adhesives, and rubber-based adhesives. Such adhesives may be of only one type or of two or more types. The adhesive layer may be of one layer or of two or more layers.
[0097] When classified according to the adhesive form, examples of the adhesive include emulsion type adhesives, solvent type adhesives, ultraviolet cross-linking type (UV cross-linking type) adhesives, electron beam cross-linking type (EB cross-linking type) adhesives, hot melt type adhesives, etc. Such adhesives may be of only one type or of two or more types.
[0098] The water vapor permeability of the adhesive layer is preferably 50 (g / (m 2 24 hours) or less, and more preferably 30 (g / (m 2 24 hours) or less, and more preferably 20 (g / (m 2 24 hours) or less, and particularly preferably 10 (g / (m2 When the water vapor permeability of the pressure-sensitive adhesive layer is within the above range, the foamed sheet of the present invention can stabilize the impact absorption property without being affected by moisture. The water vapor permeability can be measured, for example, by a method according to JIS Z 0208 under test conditions of 40°C and a relative humidity of 92%.
[0099] The adhesive constituting the adhesive layer may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of other components include other polymer components, softeners, antiaging agents, curing agents, plasticizers, fillers, antioxidants, thermal polymerization initiators, photopolymerization initiators, UV absorbers, light stabilizers, colorants (pigments, dyes, etc.), solvents (organic solvents), surfactants (e.g., ionic surfactants, silicone surfactants, fluorine surfactants, etc.), crosslinking agents (e.g., polyisocyanate crosslinking agents, silicone crosslinking agents, epoxy crosslinking agents, alkyl etherified melamine crosslinking agents, etc.). The thermal polymerization initiator and the photopolymerization initiator may be included in the material for forming the polymer component.
[0100] The foamed material of the present invention can be produced by any appropriate method, such as a method of producing the foamed material of the present invention by laminating a resin foam layer and a pressure-sensitive adhesive layer, or a method of producing the foamed material of the present invention by laminating a material for forming a pressure-sensitive adhesive layer and a resin foam layer, and then forming a pressure-sensitive adhesive layer by a curing reaction or the like. EXAMPLES
[0101] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.
[0102] [Evaluation method] <50% compression load> The measurement was performed according to the method for measuring the compression hardness of foams described in JIS K 6767. Specifically, the resin foams obtained in the examples and comparative examples were cut into test pieces of 30 mm × 30 mm size, and the stress (N) when compressed to a compression rate of 50% at a compression speed of 10 mm / min was measured per unit area (1 cm 2 ) per 25% compression load (N / cm 2 ), 50% compression load (N / cm 2 ), and
[0103] <Compressive stress retention rate (after 6 hours, after 12 hours)> Using a precision universal testing machine (Autograph AG-X plus, manufactured by Shimadzu Corporation), the resin foams obtained in the examples and comparative examples were cut into test pieces of 30 mm x 30 mm size, and the stress (N1) immediately after compressing to a compression rate of 50% at a compression speed of 10 mm / min was recorded. After the compression rate reached 50%, the displacement was held and the stress (N2) after a specified time (6 hours, 12 hours) had elapsed was recorded. The compression stress retention rate [%] was calculated using the formula: N2 / N1 x 100.
[0104] <Apparent density> The density (apparent density) of the resin foam was calculated as follows. The resin foam obtained in the examples and comparative examples was punched out to a size of 20 mm x 20 mm to prepare a test piece, and the dimensions of the test piece were measured with a vernier caliper. Next, the weight of the test piece was measured with an electronic balance. Then, the density was calculated according to the following formula. Apparent density (g / cm 3 ) = weight of test piece / volume of test piece
[0105] <Average bubble size (average cell size) and coefficient of variation of bubble size (cell size)> The resin foam was cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction). A digital microscope (product name "VHX-500", manufactured by Keyence Corporation) was used as a measuring instrument to capture an enlarged image of the bubbles in the resin foam. The image was analyzed using the analysis software of the measuring instrument to determine the number-average bubble diameter (average cell diameter) (μm). The number of bubbles in the captured enlarged image was about 400. The standard deviation was calculated from all the cell diameter data, and the coefficient of variation was calculated using the following formula. Coefficient of variation = standard deviation / average bubble size (average cell size)
[0106] <Bubble aspect ratio> A digital microscope (product name "VHX-2000, manufactured by Keyence Corporation) was used as a measuring instrument to measure the aspect ratio of the cells in the resin foams obtained in the examples and comparative examples by the following method. The resin foam is cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction), and the cut surface is measured with a microscope (for example, Keyence's "VHX-2000") to obtain a predetermined area (3 mm 2 ) area was observed at a magnification of 100x, and the length of one bubble in the thickness direction and the length TD were measured. Similar measurements were performed on all bubbles present within a given area. The aspect ratio of the bubbles is calculated by dividing the TD length by the thickness direction length. The same calculation was performed for all bubbles, and the average value was taken as the "aspect ratio of the bubbles in the resin foam."
[0107] <Bubble rate (cell rate)> Measurements were carried out in an environment with a temperature of 23°C and a humidity of 50%. The resin foams obtained in the Examples and Comparative Examples were punched out using a 100 mm x 100 mm punching blade (two processing blades (product name "NCA07", thickness 0.5 mm, blade angle 45°, manufactured by Nakayama Corporation)), and the dimensions of the punched samples were measured. In addition, the thickness was measured using a 1 / 100 dial gauge with a measuring terminal diameter (φ) of 20 mm. From these values, the volumes of the resin foams obtained in the Examples and Comparative Examples were calculated. Next, the weights of the resin foams obtained in the Examples and Comparative Examples were measured using a top-pan balance with a minimum scale of 0.01 g or more. From these values, the foam ratios (cell ratios) of the resin foams obtained in the Examples and Comparative Examples were calculated.
[0108] <Thickness of bubble wall (cell wall)> The resin foam was cut with a razor blade in the TD (direction perpendicular to the flow direction) and perpendicular to the main surface of the resin foam (thickness direction), and a digital microscope (product name "VHX-500", manufactured by Keyence Corporation) was used as a measuring instrument to capture an enlarged image of the bubble part of the resin foam, and the thickness (μm) of the bubble wall (cell wall) was determined by analyzing the image using the analysis software of the measuring instrument. The number of bubbles in the captured enlarged image was about 400.
[0109] <Non-foam bending stress> The resin foam was pressed for 5 minutes at a temperature of (melting point + 70°C) and a pressure of 15 MPa using a vacuum press molding machine (IVM-70: Iwaki Kogyosha) to obtain a non-foamed resin molded body a. Resin molded body a was cut into a sample with a width of 6 mm and a length of 50 mm. This sample was placed on a three-point bending jig with a support distance of 25 mm, and an indentation test (manufactured by Shimadzu Corporation, product name "AG-Xplus") was performed at an indentation speed of 0.5 mm / min in an environment of 23°C and 50% RH. The load (g) when the sample was indented 5 mm was recorded as the non-foaming bending stress.
[0110] <Compressive elastic modulus> Based on the compression test section of JIS K 6767, the compressibility (%) and compression resilience (kPa) of the resin foam were measured, and the compression resilience F(5%) when the compression ratio was 5% and the compression resilience F(15%) when the compression ratio was 15% were read, and the compression modulus was calculated from F(5%) and F(15%) using the formula (F(15%)-F(5%)) / (15-5)×100.
[0111] <Thickness recovery rate> Resin foam, 1000g / cm 2 The load was applied and maintained for 120 seconds, the compression was released, and the thickness of the resin foam 0.5 seconds after the release (thickness 0.5 seconds after the compressed state was released) was measured. The thickness recovery rate was calculated from the "thickness 0.5 seconds after the compressed state was released" and the thickness of the resin foam before the load was applied (initial thickness) according to the following formula. Thickness recovery rate (%) = {(thickness 0.5 seconds after releasing the compression state) / (initial thickness)} x 100
[0112] <Thickness change rate due to repeated compression> A micro servo (MMT-250NV-10, Shimadzu Corporation) was used to measure the pressure with a disk-shaped jig with a flat tip (compression attachment disk-shaped compression jig PC-5040, contact area: 4.9 cm 2 The foam was compressed 50% and 10% by repeatedly displacing the jig (IMADA Co., Ltd.), and the compression was repeated 5,000 times (initial load 0.15 N, down speed 5 min / mm, up speed 5 min / mm). The thickness after the test was measured using a digital microscope (product name "VHX-500", Keyence Corporation). The thickness before the test was Z0, the thickness after the test was Z1, and the thickness change rate due to the repeated compression was calculated using the formula (Z0-Z1) / Zo×100.
[0113] <Shock absorption rate> A test specimen was formed by placing a resin foam, double-sided tape (product number: No. 5603W, manufactured by Nitto Denko), and a PET film (product number: Diafoil MRF75, manufactured by Mitsubishi Plastics) in that order on the impact force sensor. A 66g iron ball was dropped onto the test specimen from a height of 50cm above the PET film to measure the impact force F1. In addition, an iron ball was dropped directly onto the impact force sensor as described above to measure the impact force F0 of the blank. The impact absorption rate (%) was calculated from F1 and F0 using the formula (F0-F1) / F0×100.
[0114] <Stress dispersion> FIG. 2 is a schematic cross-sectional view of a stress relaxation tester 1000 used to measure the degree of stress dispersion. As shown in FIG. 2, a polycarbonate plate (200 mm×300 mm×thickness 1 mm) 200 was placed on an iron support A, and a stress measurement film 300 (product name "Prescale" (two sheets, for low pressure (4LW), Fujifilm Corporation, a sheet with a surface that changes color when pressure is applied, 50 mm×50 mm×thickness 0.16 mm) was placed on top of the polycarbonate plate 200. Next, the resin foam obtained in the examples and comparative examples to be measured was placed on the stress measurement film 300. A structure (150 mm x 200 mm x 0.5 mm thick) 400 was placed, double-sided adhesive tape (No. 5603, Nitto Denko, 0.03 mm thick) 500 was attached on top of it, a 0.05 mm thick spacer 600 was placed, and an ABS plate (200 mm x 300 mm x 3 mm thick) 700 was placed on top. After 12 hours from the assembly, a steel ball SUS304 (φ25 mm) 800 was placed in the center on top of it, and a load of 20 N was applied for 1 minute. Thereafter, the color change of the stress measurement film 300 was observed, and those in which the color did not spread from the center of the stress measurement film 300 but was dot-like were rated C, those in which the color spread 25 mm from the center of the stress measurement film 300 were rated B, and those in which the color spread widely 50 mm from the center of the stress measurement film 300 to the edge were rated A.
[0115] Example 1 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight per 100 parts by weight of resin. After being sufficiently saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded through a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure a1 having a thickness of 0.3 mm. Furthermore, the resin foam a1 was passed between a pair of rolls (the gap between the rolls) in which one roll was heated to 200° C., to obtain a resin foam A having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam A having a thickness of 0.1 mm was obtained. The obtained resin foam A was subjected to the above evaluations, and the results are shown in Table 1.
[0116] Example 2 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 100 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 3.5 parts by weight per 100 parts by weight of resin. After being sufficiently saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded through a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure b1 having a thickness of 0.3 mm. Furthermore, the resin foam b1 was passed between the rolls (the gap between the rolls) of a pair of rolls, one of which was heated to 200° C., to obtain a resin foam B having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam B having a thickness of 0.1 mm was obtained. The obtained resin foam B was subjected to the above evaluations. The results are shown in Table 1.
[0117] Example 3 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 120 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 3.0 parts by weight per 100 parts by weight of resin. After being sufficiently saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded through a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure c1 having a thickness of 0.3 mm. Furthermore, the resin foam c1 was passed between the rolls (the gap between the rolls) of a pair of rolls, one of which was heated to 200° C., to obtain a resin foam C having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam C having a thickness of 0.1 mm was obtained. The obtained resin foam C was subjected to the above evaluations. The results are shown in Table 1.
[0118] Example 4 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1g / 10min), 75 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.8 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded from a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure d1 having a thickness of 0.4 mm. Furthermore, the resin foam d1 was passed between the rolls (the gap between the rolls) of a pair of rolls, one of which was heated to 200° C., to obtain a resin foam D having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam D having a thickness of 0.1 mm was obtained. The obtained resin foam D was subjected to the above evaluations. The results are shown in Table 1.
[0119] Example 5 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1g / 10min), 75 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 60 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.6 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded from a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure e1 with a thickness of 0.4 mm. Furthermore, the resin foam e1 was passed between the rolls (the gap between the rolls) of a pair of rolls, one of which was heated to 200° C., to obtain a resin foam E having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam E having a thickness of 0.1 mm was obtained. The obtained resin foam E was subjected to the above evaluations, and the results are shown in Table 1.
[0120] Comparative Example 1 45 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 55 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 10 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13MPa (12MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 5.5 parts by weight per 100 parts by weight of resin. After being sufficiently saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded through a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a foamed structure f1 having a thickness of 0.3 mm. Furthermore, the resin foam f1 was passed between the rolls (the gap between the rolls) of a pair of rolls, one of which was heated to 200° C., to obtain a resin foam F having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam F having a thickness of 0.1 mm was obtained. The obtained resin foam F was subjected to the above evaluations. The results are shown in Table 1.
[0121] Comparative Example 2 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40g / 10min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1g / 10min), 75 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6g / 10min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry Co., Ltd.), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at a temperature of 200°C in a twin-screw kneader manufactured by Japan Steel Works (JSW), extruded into a strand shape, cooled with water, and molded into pellets. The pellets were placed in a single-screw extruder manufactured by Japan Steel Works, and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.8 parts by weight per 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming, and then extruded through a die to obtain a sheet-like molded product. The sheet-like molded product was cut into a thin film using a slicer to obtain a resin foam G with a thickness of 0.1 mm. The obtained resin foam G was subjected to the above evaluations, and the results are shown in Table 1.
[0122] [Table 1]
[0123] As shown in Table 1, the resin foam of the present invention is excellent in "stress dispersion." Such a resin foam is advantageous in that it can prevent display unevenness due to pressure when applied to an image display device. [Industrial Applicability]
[0124] The resin foam of the present invention can be suitably used, for example, as a cushioning material for electronic devices. [Explanation of symbols]
[0125] 100 Foam material 10 Resin foam layer 20 Adhesive layer 1000 Stress relaxation tester A Iron support 200 Polycarbonate plate 300 Stress measurement film 400 Resin foam structure 500 Double-sided adhesive tape 600 Spacer 700 ABS board 800 Iron Ball
Claims
1. 50% compression load is 5N / cm 2 ~30N / cm 2 and The compressive stress retention rate after 6 hours is 50% or more, The compressive stress retention rate after 12 hours is 50% or more, Has a cellular structure, Resin foam.
2. 50% compression load is 10N / cm 2 ~30N / cm 2 The resin foam according to claim 1 .
3. The resin foam according to claim 1 or 2, having a compressive elastic modulus of 200 kPa or more.
4. The resin foam according to claim 1 , having a non-foaming bending stress of 5 MPa or more.
5. The resin foam according to claim 1 , wherein a rate of thickness change due to repeated compression is 10% or less.
6. Apparent density: 0.02 g / cm 3 ~0.50g / cm 3 The resin foam according to claim 1 ,
7. The resin foam according to claim 1 , which has a thickness recovery rate of 75% or more.
8. The resin foam according to claim 1 , wherein the aspect ratio of the cells contained in the resin foam is 1.5 or more.
9. The resin foam according to any one of claims 1 to 8, having an average cell diameter of 10 µm to 200 µm.
10. The resin foam according to claim 1 , having a foaming rate of 30% or more.
11. The resin foam according to claim 1 , wherein the coefficient of variation of cell diameter is 0.5 or less.
12. The resin foam according to any one of claims 1 to 11, wherein the thickness of the cell walls is 0.1 µm to 10 µm.
13. The resin foam according to claim 1 , comprising a polyolefin-based resin.
14. The resin foam according to claim 13 , wherein the polyolefin-based resin is a mixture of a polyolefin other than the polyolefin-based elastomer and a polyolefin-based elastomer.
15. The resin foam according to claim 1 , having a heat-fusible layer on one or both sides.
16. A pressure-sensitive adhesive layer is provided on at least one side of the resin foam layer. The resin foam layer is the resin foam according to any one of claims 1 to 15. Foam material.
Citation Information
Patent Citations
Polyolefinic resin foam and manufacturing method therefor
JP2001348452A
Polyurethane foam and water-stopping gasket
JP2007016070A
Resin foam and foam member
JP2016088977A
Polyolefin resin foam and polyolefin resin foam dustproof material using same
WO2012133288A1
Resin foam body, foam member and touch panel mounting unit
WO2015146756A1